4(6k-2)-7(k-4)=-31

Simple and best practice solution for 4(6k-2)-7(k-4)=-31 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(6k-2)-7(k-4)=-31 equation:


Simplifying
4(6k + -2) + -7(k + -4) = -31

Reorder the terms:
4(-2 + 6k) + -7(k + -4) = -31
(-2 * 4 + 6k * 4) + -7(k + -4) = -31
(-8 + 24k) + -7(k + -4) = -31

Reorder the terms:
-8 + 24k + -7(-4 + k) = -31
-8 + 24k + (-4 * -7 + k * -7) = -31
-8 + 24k + (28 + -7k) = -31

Reorder the terms:
-8 + 28 + 24k + -7k = -31

Combine like terms: -8 + 28 = 20
20 + 24k + -7k = -31

Combine like terms: 24k + -7k = 17k
20 + 17k = -31

Solving
20 + 17k = -31

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-20' to each side of the equation.
20 + -20 + 17k = -31 + -20

Combine like terms: 20 + -20 = 0
0 + 17k = -31 + -20
17k = -31 + -20

Combine like terms: -31 + -20 = -51
17k = -51

Divide each side by '17'.
k = -3

Simplifying
k = -3

See similar equations:

| 2z^2-2z+1=0 | | 3x+7=-x+7 | | -162=-8(4-8r)-5 | | 8x+4(x+10)=160 | | n/3=15/6 | | 8x+3.04=4x+10 | | -z-12=3z+12 | | (6x)(6x)=0 | | 4b=-160 | | 12.3x=152.52 | | 2g+20=6g | | 2n^2+11n-30=o | | 13(n+4-7m)= | | 4(x-2)+4=16 | | x-16.02=13.4 | | -2(-7x+1)-2x=82 | | 0.75x-0.25=0.5 | | x+14.4=28.9 | | t/3=4=2 | | 9g+9=6g | | -2(1-5x)=-14+8x | | 84=-3(3a-4) | | 84=-7(-2x-4) | | 8x+6y=3 | | (x^2)-1=2x | | 1wp=21+2 | | sin(x)=0.8164965 | | -2(x+4)-9x+7= | | x^2+2xy+y^2=7 | | 6[1-6p]+6p=-32+8p | | -4(9n+7)+11=-17-2n | | -31+a=8[2+6a] |

Equations solver categories